Obstetric characteristics of pregnancies in women 35 years old or more, according brazilian regions (Research, Society and Development, 2022)
This study aimed to investigate the obstetric characteristics of pregnancies in women aged 35 or over, according to Brazilian regions. Records of live births were recorded in the Live Birth Information System (SINASC), comprising the years 2007, 2011 and 2017. The variables were analyzed: regions, mother's age, mother's Brazilian state, type of delivery, duration of pregnancy, birth weight and some anomalies. It was observed that there is a unanimous pattern in all regions of Brazil in which the number of women who gestated aged 35 or over has increased. As for marital status, most of these pregnant women were married, a number that decreased, as well as the number of single women, and the number of women in a stable relationship increased. As for the type of delivery, in most Brazilian regions, there was an increase in cesarean deliveries in women who gestated aged 35 or more and a decrease in vaginal deliveries. In all regions of Brazil there was an increase in the number of preterm births in these women, comparing the three years. As for the babies' birth weight, the growth in the number of babies born with less than 500 grams stands out. As for the anomalies found in babies born with late pregnancies, there was a tendency to increase in frequency. It was argued, therefore, that women who are pregnant at 35 years of age or more developed complications more easily during the gestational process and the importance of prenatal care well applied to these pregnant women stands out.